The teaching of Spanish as a foreign language in China and the professors’ development - Zhen, Yang; Jiménez Cruz, Ivelissi; Montejo Lorenzo, Manuel N. (Transformación, 2024)
Objective: The paper aims at describing a developmental program for Chinese teachers of Spanish Language promoting professional performance by contextualizing current teaching methods and procedures to the Chinese university context.Methods: The study focuses on examining legal documents and teaching foreign language reference sources, and comparing the resulting theoretical framework to the teaching practice as observed and registered by one of the authors while teaching at the Hebei International Studies University.Results: The main finding is a developmental program for Chinese teachers of Spanish as a foreign language based on the antecedents and general principles of foreign language teaching and its contextualization to Chinese university education.Conclusion: The Spanish language teachers’ improvement should be characterized by the development of teaching professional competencies based on critical assimilation of the action-oriented approach (the international view), the selective assimilation of the preceding methods, the Chinese educational tradition, the vision of the Chinese education reform.
Keywords: foreign language instruction; teacher improvement; teaching methods; teacher certification